Correlation of Soil Permeability and Particale Size Distribution with Respect to Urban Stormwater Management - Kannangara, Dumal; Sarukkalige, Priyantha (Research Publishing Services, 2012)
The most challenging factor for stormwater management at source control concept is the soil permeability. Soil permeability plays an important role in this process as the infiltration values change from one place to another even in the same soil type and the same horizontal profile. The percentage availability of gravel, sand, silt and clay in a particle size distribution of a soil sample is one of the major factors that directly influence its permeability. Particle size distribution tests and laboratory permeability tests were performed for 90 randomly selected undisturbed soil samples collected at 1.5 m depth from the existing ground level. Two analyses were required to be conducted on the test results. The primary analysis of particle size distribution involved categorising them using the Unified Soil Classification system by plotting the sieve analysis graphs which were based on their percentage availability of different particle sizes. The secondary analysis investigated the relationship of soil permeability with respect to the percentage availability of silt and clay. The results indicated that the permeability value varies in a range from 0 to 20 m/day while the percentage of silt and clay varies from 0 to 10%. Moreover the secondary analysis clearly showed that soil permeability can be greatly varied in a particular range of same silt and clay percentage which might help in understanding the behaviour of soil permeability considering the other factors such as density, void ratio and porosity.